Wykorzystanie koncepcji asymptotycznej niezależności w ogonie rozkładu do analizy zależności ekstremalnej indeksów wybranych rynków akcji - Rokita, Paweł (Application of asymptotic tail independence concept in the analysis of extreme value dependence between selected stock indices, 2006)
This paper presents an empirical analysis of asymptotic tail independence for bivariate stock index return distributions. Returns from the WIG20 index and some selected indices of the leading stock markets are taken into consideration. Testing for tail independence is a stage of a research into tail dependence. The later may be of a big importance to the analysis of risk. Taking it into account may improve the quality of portfolio diversification. Thus, it may help avoiding rare-but-high losses on the portfolios that seem in the typical market conditions to be well diversified (though are not). The discussion here focuses on testing the hypothesis of asymptotic tail independence (tail dependence coefficient - TDC - equal to zero). The issue of measuring the strength of tail dependence is not investigated in this article. Measuring tail dependence may be of a big importance; it is, however, yet another step in the analysis. As it has been explained in the paper, it is not recommended to continue with estimating tail dependence without a prior verification of the tail independence hypothesis. The article is composed of two parts and a summary. The first part covers some theoretical background and a presentation of the method applied. The second part describes the empirical investigation and discusses its results.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 418-429